Pengaruh Variasi Temperatur Kerja Reaktor Terhadap Unjuk Kerja Sistem Pirolisis Sampah Plastik Low Density Polyethylene (LDPE) - Sasongko, Jaeng; Suarnadwipa, I Nengah; Murti, Made Ricki (Teknik Desain Mekanika; Vol 13 No 4 (2024): Oktober 202 :4 Teknik Desain Mekanik, 2024)
Abstract Plastic waste is the type of waste that is most often thrown away carelessly and can clog drainage channels, ditches and rivers, which can cause flooding. To reduce the negative impact of this plastic waste, it can be processed into oil which can be used as an alternative fuel. The waste processing method that can be used is pyrolysis. Pyrolysis is the process of decomposing a material at high temperatures in the absence of air or with limited air. The aim of this research is to analyze the effect of variations in reactor working temperature on the performance of the pyrolysis system which includes the rate of energy consumption for LPG fuel, oil yield capacity and mass of charcoal solids resulting from the Low Density Polyethylene (LDPE) plastic waste pyrolysis process. Pyrolysis testing with LDPE plastic as raw material, which in the test uses a pyrolysis reactor with temperatures of 200oC, 250oC, 300oC, 350oC dan 400oC, then the plastic is put into the reactor and heated. Later the plastic changes phase to gas, then the gas is cooled in the condenser which then comes out into oil and is collected in a measuring cup. After testing, it was found that the highest rate of energy consumption for LPG fuel and oil volume was at a temperature of 400oC of 4884.31 Joules/s and an oil volume of 492 ml. The higher the pyrolysis temperature, the greater the rate of LPG fuel energy consumption and the volume of oil obtained. Meanwhile, the results of observing the weight of solids were obtained, the higher the reactor temperature, the smaller the mass of solids produced. At a temperature of 400°C it produces the smallest solids of 385g. Keywords: Pyrolysis, LDPE Plastic, Fuel, Oil Capacity, Solids.